The spiritual Aspect and its Impact on Promoting Mental Health - Musa, Amna Hamid (Journal of Islamic Sciences, 2021)
This study aimed at determine the spiritual aspect and its impact on promoting the mental health of patients with Corona pandemic in the light of the Holy Qur’an and by asking the following question: What is the effect of the spiritual side in promoting the mental health of Corona pandemic patients in the light of the Holy Qur’an? The importance of the study appears in discussing one of the important topics related to the spiritual aspect inspired by the Qur’anic guidance and its use to achieve mental health. It also opens the horizons for legislative specialists to extract legislative principles in all aspects of life through research and investigation in the Holy Qur’an. One of the objective that the study to sought to achieve: to uncover the importance of caring for the spiritual side for patients with the Corona pandemic and identify aspects of promoting the mental health of its patients through attention to the spiritual aspect in light of what is mentioned in the Noble Qur’an. The study relies on the historical method as well as benefited from the descriptive and analytical method in some of its issues. The results clarify that The Muslim benefited from Corona pandemic that the affliction in its various types has a great role in raising souls, training them to endure hardships, and preparing them to face any emergency or potential circumstance. The mental training directs Muslims to follow the correct approach that achieves its desired goals. And this is to protect from aberration and sins due to Corona pandemic which causes anxiety to patients accompanied by painful psychological condition due to a person’s feeling of powerlessness in situations of frustration and conflict with disease. What is inspired by the Holy Qur’an approach to spiritual and psychological treatment is that a person should get used to adopting reasons, be patient with calamity, and never despair if there are obstacles that prevent healing.
Keywords: The spiritual aspect; Corona; prevention; treatment; The Holy Quran